AhR-mediated lipid peroxidation contributes to TCDD-induced cardiac defects in zebrafish. (March 2023) - Mi, Ping; Li, Na; Ai, Kang; Li, Lei; Yuan, Detian
Abstract: 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD), a persistent environmental contaminant that activates the aryl hydrocarbon receptor (AhR) pathway, has been reported to cause cardiac damage. However, the mechanism underlying AhR-induced cardiac defects in response to TCDD exposure remains unclear. In this study, we characterized the impacts of TCDD exposure on heart morphology and cardiac function in zebrafish. TCDD exposure in the early developmental stage of zebrafish embryos led to morphological heart malformation and pericardial edema, concomitant with reduced cardiac function. These cardiac defects were attenuated by inhibiting AhR activity with CH223191. Transcriptome profiling showed that, along with an upregulation of the AhR signaling pathway by TCDD treatment, the expression of pro-ferroptotic genes was upregulated, while that of genes implicated in glutathione metabolism were downregulated. Moreover, lipid peroxidation, as indicated by malonaldehyde (MDA) production, was increased in TCDD-exposed cardiac tissue. Accordingly, inhibiting lipid peroxidation with liproxstatin-1 reversed the adverse cardiac effects induced by TCDD treatment. Taken together, our findings demonstrate that AhR-mediated lipid peroxidation contributes to cardiac defects in the early developmental stage in zebrafish embryos exposed to TCDD. Graphical abstract: Image 1 Highlights: TCDD exposure led cardiac defects in zebrafish larvae. AhR inhibitor CH223191 restored the morphology and cardiac function induced by TCDD. Transcriptomic profiling showed upregulation of pro-ferroptotic genes and downregulation of genes implicated in glutathione metabolism. Blocking lipid peroxidation with liproxstatin-1 reversed cardiac defects induced by TCDD.